1993
DOI: 10.1021/bi00056a005
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the saccharide chains of glycolipids at the membrane surface: Conformational analysis of the glucose-ceramide and the glucose-glyceride linkages using molecular mechanics (MM3)

Abstract: Preferred conformations of the saccharide-ceramide linkage of glucosylceramides with different ceramide structures (normal and hydroxy fatty acids) were investigated by molecular mechanics (MM3) calculations and compared with conformational features obtained for glucosylglycerolipids (diacyl and dialkyl analogues). Relaxed energy map calculations with MM3 were performed for the three bonds (C1'-O1-C1-C2, torsion angles phi, psi, and theta 1) of the glucose-ceramide/diglyceride linkage at different values of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…Previous studies have shown that galactoglycerolipids, as opposed to galactosyl ceramides, are not substrates for galactose oxidase [33]. Molecular mechanics calculations of the torsional angles about the anomeric linkage in glucosyl ceramide, as opposed to glucosyl diacylglyceride [34], indicate a more extended configuration for the glycoglycerolipid which may allow tighter packing and thus restrict ligand access. Similar theoretical calculations have also predicted the restrictive influence of the plane of the membrane bilayer in glycosphingolipid recognition [35].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that galactoglycerolipids, as opposed to galactosyl ceramides, are not substrates for galactose oxidase [33]. Molecular mechanics calculations of the torsional angles about the anomeric linkage in glucosyl ceramide, as opposed to glucosyl diacylglyceride [34], indicate a more extended configuration for the glycoglycerolipid which may allow tighter packing and thus restrict ligand access. Similar theoretical calculations have also predicted the restrictive influence of the plane of the membrane bilayer in glycosphingolipid recognition [35].…”
Section: Discussionmentioning
confidence: 91%
“…The receptor role of GSLs has been hypothesized in the case of microbial infections based on their ability to interact with bacterial toxins and microbial lectins (6,7). Conformational analysis confirms that the orientation of the oligosaccharide chains of glycolipids at the cell surface complies with the possibility to interact with extracellular molecules (8,9). Indeed, synthetic analogues of GSL oligosaccharides are able to block cell-cell recognition (10).…”
Section: Glycosphingolipids (Gsls)mentioning
confidence: 89%
“…GSL carbohydrate conformation (10,94) is also restricted by the plane of the membrane (11). Membrane curvature may alter the plane of the membrane bilayer relative to the GSL carbohydrate (29,61) to affect ligand binding.…”
Section: Discussionmentioning
confidence: 99%